PERBAIKAN MESIN UNTUK MENINGKATKAN PELAYANAN BENGKEL PELABUHAN PERIKANAN NUSANTARA KECAMATAN SUNGAILIAT KABUPATEN BANGKA - Indra Feriadi; Ariyanto Ariyanto; Fajar Aswin; M Rivai (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The service of Pelabuhan Perikanan Nusantara Sungailiat workshop to fishermen was disrupted due to reduced machine availability caused by the failure of lathes, hydraulic press, drills, and grinders. This project aims to repair machine damage, so machine availability increases and workshop services return to normal.. The implementation method is carried out with corrective maintenance procedures to identify and fix the cause of damage or failure in a failed or damaged system. To verify the types of problems affecting machine’s condition using the Six Sigma DMAIC (Define-Measure-Analyze-Improve) methodology and why-why analysis. The results indicate that lathes, hydraulic presses, drills, and grinders can function well. Even though the hydraulic press machine can perform to press the product, it has not returned to the factory standard. Overall the machines can be used to provide repair services for fisherman boat engine tools/components and fishing gear. It is necessary to build a preventive maintenance system and the performance parameters of these machines so that their condition is always maintained and damage does not recur.